2015
DOI: 10.1080/07448481.2015.1042878
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Complementary and Alternative Medicine (CAM) Use Among Ivy League College Students: Implications for Student Health Services

Abstract: Ongoing assessment of CAM use can assist administrators and providers to enhance college health services and programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
(34 reference statements)
3
8
0
Order By: Relevance
“…Most respondents stated willingness to read about CAM if information were provided at the SHC itself or on the SHC website. Our study adds that female students are more willing to seek further information about CAM from brochures and from physicians, consistent with a recent study that indicated that female students with positive attitudes toward CAM are more likely to use it [7]. Moreover, compared to non-CAM users, CAM users are more likely to state that they desired that physicians provide advice about CAM, suggesting those who have already tried CAM desire to use it responsibly.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most respondents stated willingness to read about CAM if information were provided at the SHC itself or on the SHC website. Our study adds that female students are more willing to seek further information about CAM from brochures and from physicians, consistent with a recent study that indicated that female students with positive attitudes toward CAM are more likely to use it [7]. Moreover, compared to non-CAM users, CAM users are more likely to state that they desired that physicians provide advice about CAM, suggesting those who have already tried CAM desire to use it responsibly.…”
Section: Discussionsupporting
confidence: 89%
“…anorexia nervosa, bulimia nervosa) and not necessarily for health maintenance and promotion. Expanding insurance coverage is a potential method to increase access to CAM modalities, but decisions regarding whether or not student health centers should offer certain CAM modalities are complex and depend on multiple factors including demand, cost, and treatment efficacy [7]. In addition, it is unclear if students are aware of the scope of their insurance coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is similar with Awad's research in which CAM usage rate was found to be 55.2% in university students [1]. In another research made by Columbia university CAM usage in the last 12 years has been found as 82%, this result is higher than our result but this fact can be explained by the CAM perception in the researches [26]. The first three usage statements of the herbal treatment applications are; products which strengthen the body and immune system (31,3%), skin care products (31,3%) and hair care products (22,3%) (Graphic 1).…”
Section: Discussionsupporting
confidence: 90%
“…Respondents were 83% graduate students (17% of these were preprofessional) and 17% undergraduate students. 12 Across all samples, the patients most likely to report using these modalities were women and students with family members who had used a CAM modality.…”
Section: Student Interestmentioning
confidence: 96%